2017
DOI: 10.1002/2017pa003143
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Signals in Carbon Isotopes: Phase Distortion as a Signature of the Carbon Cycle

Abstract: Isotopic mass balance models are employed here to study the response of carbon isotope composition (δ13C) of the ocean‐atmosphere system to amplitude‐modulated perturbations on Milankovitch time scales. We identify a systematic phase distortion, which is inherent to a leakage of power from the carrier precessional signal to the modulating eccentricity terms in the global carbon cycle. The origin is partly analogous to the simple cumulative effect in sinusoidal signals, reflecting the residence time of carbon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 99 publications
1
10
0
Order By: Relevance
“…lithological) tuning signals can produce more accurate age models in comparison with age models based on globally integrated isotope records. The latter data are known to produce significant lags relative to eccentricity as a result of highly non-linear feedback mechanisms (Laurin et al, 2017;Pälike et al, 2006b;Zeebe et al, 2017), a result that is confirmed by this study (Table 2). The independent evidence that we provide for using a lithological (proxy) record for the astronomical age calibration of marine sediments yields further support for similar astronomical tuning methods.…”
Section: Evaluation Of Tuning Signalssupporting
confidence: 86%
See 2 more Smart Citations
“…lithological) tuning signals can produce more accurate age models in comparison with age models based on globally integrated isotope records. The latter data are known to produce significant lags relative to eccentricity as a result of highly non-linear feedback mechanisms (Laurin et al, 2017;Pälike et al, 2006b;Zeebe et al, 2017), a result that is confirmed by this study (Table 2). The independent evidence that we provide for using a lithological (proxy) record for the astronomical age calibration of marine sediments yields further support for similar astronomical tuning methods.…”
Section: Evaluation Of Tuning Signalssupporting
confidence: 86%
“…7b; Laurin et al, 2017). On both the initial magnetostratigraphic age model and on the CaCO 3 tuned age model, the phase lag, as visually identified in the filtered records, between the 405 kyr eccentricity cycle and the 405 kyr cycle in δ 13 C increases during the early Miocene (Figs.…”
Section: Astronomical Tuning Using the Benthic Foraminiferal δ 13 C Rmentioning
confidence: 87%
See 1 more Smart Citation
“…8A, C, D). The difference between the direct filter and the filter of the AM is explained by the residence time of carbon in the ocean, which creates a delay in the response of the  13 C to the orbital forcing (Laurin et al, 2017). In this context of hemipelagic sediments, with the limestone beds originating from exports from neritic environments, the difference may also be due to the change of the carbonate source.…”
Section: Astrochronology Of the The Polymorphum Zonementioning
confidence: 99%
“…The duration of this interval in the El Portón section is calculated at 2.15 myr, in good agreement with the Tethyan area ( Figures 10-12). The difference of 0.04 myr between the two areas may be due to the uncertainties of the correlations between the Andean and the Tethyan areas, and to the fact that the early-late Hauterivian boundary may be located within the non-marine Avilé (Laurin et al, 2017) and from the change in the source of carbonate, which change the phasing of carbonate δ 13 C relative to the insolation (Martinez, 2018). Thus, the reliable…”
Section: Implications For the Next Geological Time Scale In The Earlymentioning
confidence: 99%